2012
DOI: 10.3892/ol.2012.789
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Burkitt’s lymphoma in a child: A rare case

Abstract: Abstract. Burkitt's lymphoma (BL) is a high-grade lymphoma which represents 8-10% of all tumors in individuals younger than 15 years old. It may occur as an abdominal tumor, which in rare cases may include gastric mucosa, although in most cases, the tumor is located in the ileum or cecum. Primary gastric lymphoma constitutes as low as 1.48% of all gastric cancers in children. In this study, we described a case of gastric BL in a 4-year-old child, presenting discontinuous abdominal pain, weight loss, constipati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Their study showed that the ratio of male patients is higher than female. Chlidren cases have been reported by Angotti R, Kim SC et.al (13,14). A retrospective analysis showed that gastric BL often involves body and antrum of stomach (15).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Their study showed that the ratio of male patients is higher than female. Chlidren cases have been reported by Angotti R, Kim SC et.al (13,14). A retrospective analysis showed that gastric BL often involves body and antrum of stomach (15).…”
Section: Discussionmentioning
confidence: 95%
“…These two types usually affect extranodal sites (such as bone marrow and GI-tract) and CNS (especially the pia mater) (20,21). According to previous case reports, most patients with gastric BL have mild symptoms even though lesions of the stomach are serious (11,13,14). But the disease can progress very quickly and some serious symptoms appear, such as gastrointestinal bleeding and di culty swallowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-Hodgkin lymphoma (NHL) is the third most common cancer (10%), accounting for ~60% of all lymphomas in children and adolescents (1). The most common symptoms of pediatric NHL are fever, superficial lymph node enlargement, cough, shortness of breath, anorexia, abdominal pain, sore throat and nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%